Intraspecific Variation and Recent Loss of Ancient, Conserved Effector Genes in the Sudden Oak Death Pathogen Phytophthora ramorum - Nicholas C. Cauldron; Caroline M. Press; Alexandra J. Weisberg; Marília Horta Jung; Tamara Corcobado; Joan F. Webber; Koji Kageyama; Ayaka Hieno; Hayato Masuya; Seiji Uematsu; Bruno Scanu; Clive M. Brasier; et al. (Molecular Plant-Microbe Interactions, 2025)
Members of the Phytophthora genus are responsible for many important diseases in agricultural and natural ecosystems. Phytophthora ramorum causes devastating diseases of oak and tanoak stands in U.S. forests and larch in the United Kingdom. The four evolutionary lineages involved express different virulence phenotypes on plant hosts, and characterization of gene content is foundational to understanding the basis for these differences. Recent discovery of P. ramorum at its candidate center of origin in Asia provides a new opportunity for investigating the evolutionary history of the species. We assembled high-quality genome sequences of six P. ramorum isolates representing three lineages from Asia and three causing epidemics in Western U.S. forests. The six genomes were assembled into 13 putative chromosomes. Analysis of structural variation revealed multiple chromosome fusion and fission events. Analysis of putative virulence genes revealed variations in effector gene composition among the sequenced lineages. We further characterized their evolutionary history and inferred a contraction of crinkler-encoding genes in the subclade of Phytophthora containing P. ramorum. There were losses of multiple families and a near complete loss of paralogs in the largest core crinkler family in the ancestor of P. ramorum and sister species P. lateralis. Secreted glycoside hydrolase enzymes showed a similar degree of variation in abundance among genomes of P. ramorum lineages as that observed among several Phytophthora species. We found plasticity among genomes from multiple lineages in a Phytophthora species and provide insights into the evolutionary history of a class of anciently conserved effector genes. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.